Formulasi Sediaan Antijerawat Ekstrak Daun Pepaya (Carica papaya L.) dalam Bentuk Gel - Romelli, Hamalatul Qur’ani; Darsono, Farida L; Soegianto, Lisa (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2020)
The purpose of this study was to determine the concentration of papaya (Carica papaya L.) leaf extract which gave antibacterial activity and to determine the effect of increasing concentrations of papaya (Carica papaya L) leaf extract on physical quality, effectiveness of antibacterial inhibition and stability in the gel form. The antibacterial activity was tested using the well method. The evaluations consist of physical quality tests including organoleptic, pH, homogeneity, dispersion and viscosity; effectiveness (antibacterial activity); safety; acceptability and stability (organoleptic, pH and viscosity). The results showed that the higher the concentration of extract of papaya leaf, the higher the antibacterial activity and also influenced its physical quality and the stability. The concentration of papaya leaf extract (Carica papaya L) which have the highest antibacterial activity is 30%. The increasing of the concentration of papaya leaf extract (Carica papaya L.) affected the physical quality (pH, viscosity and dispersion), the effectiveness (antibacterial activity) and stability (pH stability and viscosity stability). The best formula in this study is formula 2 (papaya leaf extract 20%) which fulfill requirements of physical (organoleptic), pH, viscosity, dispersion, homogeneity, have antibacterial activity, safety and stability test